Türkiyede siyasî partiler, 1859-1952 - Tunaya, Tarık Zafer, 1916-1991. (İstanbul)
4 kitap 1 ciltte (viii, 78 sayfa, 1. kitap sayfa 79-160 ; 2. kitap sayfa 160-471 ; 3. kitap 472-539 ; 4. kitap sayfa 540-799)